A collection of experimental data for aerosol monitoring cyclones. Issue 10 (3rd October 2017) - Kenny, L. C.; Thorpe, A.; Stacey, P.
ABSTRACT: Cyclone behavior is complex and difficult to model. Recent years have seen the development of new and better predictive models for cyclone performance, which are providing new insights into how cyclone performance is affected by cyclone geometry. Experimental data are essential for verification of such models. In this article we present a dataset of more than 250 experimental determinations of cyclone penetration. The dataset includes cyclones with a wide range of sizes and geometries, tested at a wide range of flow rates. We illustrate some empirical, semi-empirical and mathematical approaches to modeling these cyclone data. For our data, we show that mathematical modeling approaches developed for large gas-cleaning cyclones can also be applied to small aerosol monitoring cyclones, to diverse cyclone geometries, and laminar flow operating conditions. Copyright © Crown copyright